2011
DOI: 10.3155/1047-3289.61.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Modeling in California with Two Chemical Mechanisms: Model Intercomparison and Response to Emission Reductions

Abstract: An updated version of the Statewide Air Pollution Research Center (SAPRC) chemical mechanism (SAPRC07C) was implemented into the Community Multiscale Air Quality (CMAQ) version 4.6. CMAQ simulations using SAPRC07C and the previously released version, SAPRC99, were performed and compared for an episode during JulyAugust, 2000. Ozone (O 3 ) predictions of the SAPRC07C simulation are generally lower than those of the SAPRC99 simulation in the key areas of central and southern California, especially in areas where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Cai et al . [] also indicated that the NO x disbenefit areas are spatially expanded using the condensed version of SAPRC07. Using observable indicators [ Liang et al ., ] and ozone production efficiencies calculated by ambient concentration measurements may provide another independent measure of ozone sensitivities to precursors. Forest fire emissions were found to be important ozone precursors and can interact with urban emissions [ Pfister et al ., ; Bein et al ., ; Jaffe and Wigder , ; Strada et al ., ; Singh et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cai et al . [] also indicated that the NO x disbenefit areas are spatially expanded using the condensed version of SAPRC07. Using observable indicators [ Liang et al ., ] and ozone production efficiencies calculated by ambient concentration measurements may provide another independent measure of ozone sensitivities to precursors. Forest fire emissions were found to be important ozone precursors and can interact with urban emissions [ Pfister et al ., ; Bein et al ., ; Jaffe and Wigder , ; Strada et al ., ; Singh et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Cai et al . [] also indicated that the NO x disbenefit areas are spatially expanded using the condensed version of SAPRC07. Using observable indicators [ Liang et al ., ] and ozone production efficiencies calculated by ambient concentration measurements may provide another independent measure of ozone sensitivities to precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complex nature of O 3 chemistry and emissions source mixes in a given urban area, photochemical grid models provide a credible tool for evaluating responsiveness to emissions changes and have been used extensively for O 3 planning purposes in the past (Cai et al 2011; Hogrefe et al 2011; Kumar and Russell 1996; Simon et al 2012). In the present study, we used a photochemical grid model applied in three different urban areas to illustrate temporal and spatial patterns of O 3 and how those patterns may change as a result of reduced precursor emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical mechanism selection has been a difficult issue for regulatory policy development since the early days [2]. These concerns still exist [3,4]. These difficulties are compounded by the often limited choice of chemical mechanisms available within the widely used air quality modelling systems because chemical mechanisms are not offered on a plug-and-play basis as with meteorological parameterisations, for example.…”
Section: Introductionmentioning
confidence: 99%